Answer: (-20,-10) Step-by-step explanation: [tex]( – 10 \: \: – 3) = ( \frac{0 + x}{2} \: \: \frac{4 + y}{2} )[/tex] Solve for.x coordinate [tex] – 10 = \frac{0 + x}{2} \\ – 20 = 0 + x \\ x = – 20[/tex] solve for y coordinate [tex] – 3 = \frac{4 + y}{2} \\ – 6 = 4 + y \\ – 10 = y[/tex] Log in to Reply

Answer:(-20,-10)

Step-by-step explanation:[tex]( – 10 \: \: – 3) = ( \frac{0 + x}{2} \: \: \frac{4 + y}{2} )[/tex]

Solve for.x coordinate

[tex] – 10 = \frac{0 + x}{2} \\ – 20 = 0 + x \\ x = – 20[/tex]

solve for y coordinate

[tex] – 3 = \frac{4 + y}{2} \\ – 6 = 4 + y \\ – 10 = y[/tex]